Effect of supplementation of L-carnitine during in vitro maturation on embryo production in Sahiwal cows - Singh, Dr. Khushpreet; Dr Narinder Singh; Dr Gurjot Kaur Mavi (The Indian Journal of Animal Sciences, 2026)
Embryo transfer technology enables the rapid dissemination of superior genetics and in vitro produced embryos have gained more consideration than the in vivo derived embryos due to higher yield of embryos with respect to time. The primary limitation impacting in vitro derived embryos is the success of in vitro maturation as in vitro derived oocytes contain more lipid content contributing to increased oxidative stress and compromised developmental competence. Lipid modulator, L-carnitine at 1 mM and 3 mM was supplemented in the maturation media with the view to decrease lipid content and subsequent oxidative stress in the oocytes undergoing maturation. A total of 326 follicles were aspirated out of which 228 cumulus oocyte complexes (COCs) were collected at a recovery rate of 69.93%.  The in vitro maturation of the COC’s supplementation with 3 mM L-Carnitine exhibited (n, %) significantly (p